Electrowetting on dielectric (EWOD) properties of Teflon-coated electrosprayed silica layers in air and oil media and the influence of electric leakage. Issue 25 (20th June 2018) - Kim, Jae-Hun; Lee, Jae-Hyoung; Kim, Jin-Young; Mirzaei, Ali; Wu, Ping; Kim, Hyoun Woo; Kim, Sang Sub
Abstract : Schematic of the EWOD set-up in air; changes of the WCAs in air upon the application of different voltages. Abstract : This paper reports the electrowetting (EW) properties of silica layers. Rough silica layers were deposited on a Si substrate by the electrospraying of SiO2 for different times (10 s–10 min) and subsequently Teflon coated with different thicknesses (35 and 625 nm). The surface roughness measurements revealed an increase in roughness with increasing electrospraying time. A thinner (35 nm) Teflon-coated layer showed better EW properties and was selected for subsequent studies. By applying different voltages (0–200 V) to the thinner Teflon-coated rough SiO2 layers, the water contact angle (WCA) decreased continuously and the SiO2 layer that had been electrosprayed for 20 s showed the maximum decrease in WCA in air, whereas the wetting behavior changed from hydrophobic to hydrophilic under a voltage of 200 V. In addition, the EW behavior of the SiO2 layers in oil ambient was studied and it was found that under the maximum applied voltage (150 V), both 20 and 30 s electrosprayed layers exhibited hydrophilic behavior. These results showed that electric leaking currents, which are largely ignored, can be used to tailor the relationship between the WCA and applied voltage: from a non-linear ( V 2 ) to a linear ( V ) function. In particular, a decrease in the WCA equals the applied voltage normalized to the maximum (or breakdown) external voltage. This study opens a new research field in materials chemistry with regards to the coupling of electrochemical, thermodynamic and mechanical interactions.